Forecast of the Impact of Electric Car Battery Performance and Infrastructural and Demographic Changes on Cumulative Accessibility for the Five Most Populous Cities in Poland - Piotr Rosik; Sławomir Goliszek; Tomasz Komornicki; Patryk Duma (Energies, 2021)
The purpose of this study is to compare (1) technological factors (the ranges offered by the batteries of three popular electric vehicles in Poland); (2) infrastructure improvements; and (3) demographic changes and their impact on accessibility in the context of the ranges of labor markets within the 30, 60, and 90 min isochrones in moderate driving mode for the five largest cities in Poland using cumulative accessibility. We conclude that technological developments result in a much greater improvement in accessibility than demographic and infrastructural change. This is already visible with the 30 to 60 min isochrones, in particular when using the BMW in Cracow (with a more than 36% improvement in accessibility). Even greater changes, reaching as much as over 90%, are observed for the 60–90 min isochrones. The analysis shows that the shift in electromobility may be constrained by parallel demographic processes, dispersion of population in suburban areas, and the development of road infrastructure. The novelty of the approach stems from the fact that it is based on three above mentioned key factors that influence the accessibility of labor markets for EV users in the largest cities up to 2030.